Model-fitting approach for methylene blue dye adsorption on and seeds-derived adsorbents - Sunanda Sharma; DP Tiwari; KK Pant (Adsorption Science & Technology)
Adsorption of methylene blue dye over the adsorbent derived from Sapindus seed hull (S) and Camelina (C) is studied. Batch adsorption study on both adsorbents is compared as a function of various parameters such as time, initial concentration and temperature. Langmuir and Freundlich models were fitted to the equilibrium data of methylene blue dye adsorption. Kinetics was evaluated using pseudo-first- and second-order models. Weber Morris model helped to understand the intraparticle diffusion during adsorption of methylene blue molecules. Thermodynamic analysis on both adsorbents revealed the spontaneity of the process. The relative study illustrated a comparison in adsorption capacities among both the adsorbents. Morphology explicated the surface characteristics of both the sorbents. Fourier transform infrared spectroscopy spectrum revealed a variety of functional groups on adsorbents’ surface.